Effect of 50 Hz magnetic field exposure on the adherent cell contacts of primary mouse Leydig cells in culture - Forgács, Zsolt (Acta Biologica Szegediensis, 2003)
Mouse primary testicular intersitital (Leydig) cells obtained from 30-35 g NMRI mice were exposed in a CO2 incubator to a sinusoidal 50 Hz/100 µT magnetic field for 48 h. Non-exposed, human choriogonin stimulated (0.1 mIU/ml hCG) cells were also cultured as positive controls. Cells were grown as monolayer on cover slips posited on the bottom of the plastic 24-well culture plates. Following the incubation the cells were fixed and permeabilized with -20ºC methanol for 2 hours. For immunocytochemical detection of cadherins, ß-catenin and tubulin, cells were incubated over 60 minutes at room temperature with (1:300 diluted) pan-cadherin, anti-ß-catenin or antitubulin. Anti-mouse FITC developed in rabbit was used as secondary antibody. Evaluating the samples by fluorescent microscopy, we found that the applied magnetic field exposure increased the amounts of cadherins and ß-catenin along the surface of the cell-to-cell contacts. The amount of microtubuli was also elevated and typical shape of cells was changed. The effects of magnetic field exposure were similar to those caused by hCG in the positive controls. Further investigations are required to clarify the subcellular action of applied magnetic field in Leydig cells.